Thermal Performance Analyses of Multiborehole Ground Heat Exchangers. (11th December 2017) - Luo, Wanjing; Tang, Changfu; Feng, Yin; Miao, Pu
Abstract : Geothermal energy known as a clean, renewable energy resource is widely available and reliable. Ground heat exchangers (GHEs) can assist the development of geothermal energy by reducing the capital cost and greenhouse gas emission. In this paper, a novel semianalytical method was developed to study the thermal performance of multiborehole ground heat exchangers (GHEs) with arbitrary configurations. By assuming a uniform inlet fluid temperature (UIFT), instead of uniform heat flux (UHF), the effects of thermal interference and the thermal performance difference between different boreholes can be examined. Simulation results indicate that the monthly average outlet fluid temperatures of GHEs will increase gradually while the annual cooling load of the GHEs is greater than the annual heating load. Besides, two mechanisms, the thermal dissipation and the heat storage effect, will determine the heat transfer underground, which can be further divided into four stages. Moreover, some boreholes will be malfunctioned; that is, boreholes can absorb heat from ground when the GHEs are under the cooling mode. However, as indicated by further investigations, this malfunction can be avoided by increasing borehole spacing.